IOS components and frameworks : understanding the advanced features of the iOS SDK - Richter, Kyle (Developer's library., 2014)
Take Your Next Leap Forward as an iOS App Developer! Covers iOS 7 and Xcode 5 iOS Components and Frameworks will help you leverage iOS's powerful components and frameworks to build apps with outstanding performance, reliability, interactivity, media support, and customization. Pioneering iOS developers Kyle Richter and Joe Keeley illuminate the sophisticated intermediate-to-advancedlevel techniques you're now ready for. You'll find example-rich coverage of topics ranging from social support to security, Core Data, TextKit, iCloud support, UIKit Dynamics, MapKit, and Passbook. There's also a complete section on advanced performance and security, including the effective use of Grand Central Dispatch and Keychain. Each chapter contains a complete sample project that walks you through integrating its technology into a typical iOS app. You'll discover how multiple iOS features can be combined into exceptionally powerful apps and walk through a complete case study project: a fully functional game with complete Game Center integration. Coverage includes: New physics-based animation effects provided by UIKit Dynamics Making the most of Core Location, MapKit, and Geofencing Leveraging Game Center features such as Leader Boards and Achievements Giving users access to their address and media libraries from within your app Using lightweight JSON to move data among servers, apps, and websites Syncing apps via iCloud using UIDocument and key-value store syncing Securing user data with Keychain Informing users of important app-related events via Notifications Storing and retrieving persistent data locally with Core Data Using advanced Objective-C features to write more manageable, concise apps Improving responsiveness through concurrency with Grand Central Dispatch Advanced text handling and display with TextKit Smoothly handling complex and continuous gestures Effective debugging techniques with Xcode 5 and Instruments Building passes for Passbook and PassKit If you're a serious iOS developer who wants to build cutting-edge apps, iOS Components and Frameworks delivers the practical skills, reusable code, and expert insights you're looking for.